2022
DOI: 10.3389/fimmu.2022.900522
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Immune Checkpoint Blockade Plus Interferon-Γ Add-On Antifungal Therapy in the Treatment of Refractory Covid-Associated Pulmonary Aspergillosis and Cerebral Mucormycosis

Abstract: Invasive fungal diseases (IFD) still cause substantial morbidity and mortality, and new therapeutic approaches are urgently needed. Recent data suggest a benefit of checkpoint inhibitors (ICI). We report the case of a diabetic patient with refractory IFD following a SARSCoV-2 infection treated by ICI and interferon-gamma associated with antifungal treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…Similarly, combinatorial immunotherapy with nivolumab and IFN-γ was reported in a 56-year-old diabetic patient with COVID-19 who had received dexamethasone and tocilizumab (anti-IL-6) and developed invasive pulmonary aspergillosis one week after intensive-care unit (ICU) admission, later complicated by two Mucoralean brain abscesses and ethmoidal sinusitis ( 55 ). The brain lesions were insufficiently responsive to combined antifungal therapy with liposomal amphotericin B and triazoles, and only partially accessible for surgical debridement.…”
Section: The Growing Promise Of Icis In Medical Mycologymentioning
confidence: 79%
See 2 more Smart Citations
“…Similarly, combinatorial immunotherapy with nivolumab and IFN-γ was reported in a 56-year-old diabetic patient with COVID-19 who had received dexamethasone and tocilizumab (anti-IL-6) and developed invasive pulmonary aspergillosis one week after intensive-care unit (ICU) admission, later complicated by two Mucoralean brain abscesses and ethmoidal sinusitis ( 55 ). The brain lesions were insufficiently responsive to combined antifungal therapy with liposomal amphotericin B and triazoles, and only partially accessible for surgical debridement.…”
Section: The Growing Promise Of Icis In Medical Mycologymentioning
confidence: 79%
“…Under isavuconazole only, cerebral mucormycosis progressed and the patient deteriorated. The authors discussed that earlier salvage immunotherapy might have had a stronger immunological and clinical impact and underscored the need to study optimal timing of antifungal ICI therapy in the setting of underlying antifungal therapy ( 55 ).…”
Section: The Growing Promise Of Icis In Medical Mycologymentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody and Tcell responses after COVID-19 vaccinations in a majority of solid tumor patients were equivalent to those of healthy donors [15]. A case report of a diabetic patient with refractory invasive fungal diseases after SARS-CoV-2 infection demonstrated that treatment with ICI and interferon greversed T cell exhaustion and enhance leukocytes activation, whereas careful consideration in immune-mediated adverse events is needed [16]. A cohort study in cancer patients demonstrated that the immune response to COVID vaccination is independent of the anti-cancer immune response in ICI treatment [17].…”
Section: Icis and Covid-19mentioning
confidence: 93%
“…Several recent studies have suggested the relationship between ICIs and COVID-19 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18).A melanoma patient treated with nivolumab, an ICI, and bempegaldesleukin, PEGylated interleukin-2 (IL-2), developed COVID-19 pneumonia with no serious adverse outcome [9], however, modification of the immune response to COVID-19 by treatment with ICIs and bempegaldesleukin has been suggested [9]. Treatment with ICIs, tocilizumab plus pembrolizumab showed decreased time to clinical improvement in COVID-19 patients [10,11].Patients with lung cancer treated with ICIs demonstrated no increased incidence of immune-related adverse events associated with mRNA vaccines, while the vaccine immunogenicity was lower [12].…”
Section: Icis and Covid-19mentioning
confidence: 99%